Strategic Planning for Recruitment and Retention of Older African Americans in Health Promotion Research Programs - Dreer, Laura E. (2014)
The purpose of this study was to 1) describe a strategic plan for recruitment and retention used in conducting eye health education research with African-Americans living in urban and rural areas of Alabama and 2) characterize recruitment and retention patterns for this community-based project. We evaluated an eye health education program tailored specifically to older African Americans. InCHARGE© was designed to promote eye disease prevention by conveying the personal benefits of annual, dilated, comprehensive eye care and teaching strategies to minimize barriers to regular eye care. The InCHARGE© program or a social contact control program was delivered at 20 senior centers in predominately African American urban and rural communities. From pooled data across three studies, 380 African Americans completed a questionnaire about knowledge and attitudes/beliefs about eye disease and eye care before the program and by telephone at either 3 or 6 months after the presentation. The project consisted of 4 phases and a total of 10 strategic objectives for recruitment as well as retention of older African Americans that were implemented in a systematic fashion. Overall, retention rates for follow-up at either 3 or 6 months were 75% and 66% respectively. African Americans from rural areas were more likely to be lost to follow-up compared to those from urban areas. We discuss the benefits of utilizing a strategic plan that serves to address problems with underrepresentation of minorities in clinical research.